2020
DOI: 10.1021/acs.jmedchem.0c01506
|View full text |Cite
|
Sign up to set email alerts
|

Proline Hinged Amphipathic α-Helical Peptide Sensitizes Gram-Negative Bacteria to Various Gram-Positive Antibiotics

Abstract: Gram-negative bacteria are becoming resistant to almost all currently available antibiotics. Systemically designed antimicrobial peptides (AMPs) are attractive agents to enhance the activities of antibiotics. We constructed a small Pro-scanning library using amphipathic model peptides. Measurements of minimum inhibitory concentration (MIC) against Escherichia coli and hemolytic activities showed that one of the Pro-hinged peptides, KL-L9P, displays the highest specificity toward E. coli. Moreover, KL-L9P sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…In addition, the substitution by proline leads to the weakening of the antimicrobial ability of T1CEh-KKP except for against S. aureus . However, it was found that α-helical AMPs that possess hinge conformations showed stronger antimicrobial selectivity against Gram-negative bacteria than the linear AMPs [ 41 , 42 ]. The proline at position 14 of melittin was proved to contribute the binding to the membrane as well as the lytic activity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the substitution by proline leads to the weakening of the antimicrobial ability of T1CEh-KKP except for against S. aureus . However, it was found that α-helical AMPs that possess hinge conformations showed stronger antimicrobial selectivity against Gram-negative bacteria than the linear AMPs [ 41 , 42 ]. The proline at position 14 of melittin was proved to contribute the binding to the membrane as well as the lytic activity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The desired product was obtained as a yellow oil (30.1 mg, 85%). 1 (S,E)-N-Butyl-4-(4-(3,7-dimethyl-3-vinylocta-1,6-dien-1-yl)phenoxy)butan-1-amine (15). Compound 15 was synthesized from 2 (43 mg, 0.11 mmol) and n-butylamine (1 mL), according to the procedure used to prepare 5.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Cationic antimicrobial peptides (CAMPs), known as host defense peptides (HDPs), are important components of the mammalian innate immune system. CAMPs have several obvious advantages, including rapid bactericidal action, broad-spectrum antibacterial activity, and low bacterial resistance, which are considered to be the most potential substitutes for antibiotics. Most of CAMPs have cationic amphiphilic topological structures composed of less than 50 amino acids. , Unlike zwitterionic mammalian cell membranes, the surface of the bacterial cell membrane is negatively charged. , The phospholipid molecules contained in the bacterial cell membrane are mainly negatively charged cardiolipin and phosphatidylglycerol, as well as electrically neutral phosphatidylethanolamine. , The positively charged moieties of CAMPs are electrostatically attracted to the negatively charged bacterial cell membrane; then, the hydrophobic moieties of CAMPs can insert into the phospholipid bilayer of bacterial cell membrane through hydrophobic interaction, leading to the leakage of the intracellular contents and bacterial cell death. ,, CAMPs possess many obvious advantages, but their inherent shortcomings, including high manufacturing cost, poor in vivo stability, and low in vivo efficacy, seriously limit their potential clinical applications. , …”
Section: Introductionmentioning
confidence: 99%
“…However, there are some major hurdles in the development of these host defense antimicrobial peptides as alternatives to antibiotics against these pathogens. Thus, despite a huge amount of work being carried out in this area, it continues to be a challenging task to identify, design, and synthesize novel antimicrobial peptides with broad-spectrum antimicrobial activities, cell selectivity, and stability under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%